TIME, PALS!; AN APPLICATION-BASED TOOL TO REDUCE ACADEMIC PROCRASTINATION AMONG LEARNERS. - Raisha Anindra Raza; Indah Nuriman (Journal of International Islamic Law, Human Right and Public Policy, 2025)
Education is very important in shaping the quality of reliable Human Resources Development (HRD) who are ready to face future challenges. However, students often experience difficulties in managing their time, which can cause procrastination, a problem that hampers productivity and academic performance. Procrastination can increase stress levels and have a negative impact on academic achievement, with delayed tasks often completed with unsatisfactory results. With technological advances, mobile applications for time management such as 'Time, Pals!' offer a potential solution through features like a time table, to-do list, and school schedule that are designed using Python, Editor/IDE, and PostgreSQL. This application is designed and is hoped to help in organizing the tasks of students and it is hoped that with the existence of this application, students can reduce procrastination.